A review on microbiological and technological aspects of Serpa PDO cheese: An ovine raw milk cheese - Araújo-Rodrigues, Helena (2020)
Serpa is a PDO cheese considered one of most popular and relevant traditional Portuguese cheeses due to its unique aroma and flavour, which are very much-appreciated characteristics. The special and recognised sensorial attributes of Serpa cheese are a result of the ingredients used, coupled with the manufacturing process, specifically raw ovine milk and extracts of Cynara cardunculus L. as coagulant, without addition of any starter culture or milk pasteurisation. Serpa quality and safety issues, linked to the high susceptibility and heterogeneity of its final sensorial attributes fosters the importance of large-scale studies focused on biochemical and microbial aspects. Despite the scientific relevance of this traditional product, Serpa studies are still very scarce and limited with the cheesemaking procedure lacking in regulation. Accordingly, the present work emphasises the current knowledge on Serpa PDO cheese, giving an overview and critical analysis of existing studies and discussing Serpa technological process.